Converting Technology to Mitigate Environmental Damage - Levi, Maurice D.; Nault, Barrie R. (Management Science, 2004)
There are many situations where policy makers would like to induce firms to make a major discrete conversion in production technology to help the environment. This paper examines how heterogeneity in the operating condition of firms' plant and equipment, which cannot be observed by policy makers, can affect the choice between incentives to encourage conversion to a cleaner technology. By relating different conditions of firms' plant and equipment to production costs, extent of environmental damage, and cost of conversion to a cleaner technology, we show when a perfectly discriminating incentive to encourage conversion is not feasible. In addition, we show that firms with plant and equipment in better condition will convert their technology to mitigate their environmental damage, and firms with plant and equipment in poorer condition will not. This and a series of additional results lead to conditions under which an administratively simple uniform lump-sum incentive to switch to cleaner technology is preferable to one based on output. These results and conditions extend to cases where there are network externalities in conversion, and where there is strategic timing in firms' choice of when to convert.